2004
DOI: 10.1002/hed.20109
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis to the submandibular gland in head and neck carcinomas

Abstract: Because the submandibular gland has no intraparenchymal lymph nodes, its involvement in upper aerodigestive tract carcinomas must be through extension from a locally involved lymph node or the primary tumor. Previous work has demonstrated that the submandibular gland can undergo transplantation out of the neck with subsequent reimplantation, as a possible means of protection from the effects of radiation. We demonstrated the submandibular gland to be involved only in cases of ipsilateral oral cavity tumors or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
42
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 16 publications
(9 reference statements)
6
42
0
1
Order By: Relevance
“…Spiegel et al 4 mentioned that there are no intraparenchymal lymph nodes, whereas DiNardo 5 and Lim et al 6 presented 6 different groups of lymph nodes: preglandular, prevascular, retrovascular, retroglandular, deep, and intraglandular.…”
mentioning
confidence: 99%
“…Spiegel et al 4 mentioned that there are no intraparenchymal lymph nodes, whereas DiNardo 5 and Lim et al 6 presented 6 different groups of lymph nodes: preglandular, prevascular, retrovascular, retroglandular, deep, and intraglandular.…”
mentioning
confidence: 99%
“…As previously demonstrated in an experimental series [28,29] and in a clinical setting, in patients with severe keratoconjunctivitis [21][22][23][24]26] where one gland was transplanted to the temporal region and the submandibular duct connected to the lateral conjunctival fornix, this denervation had no detrimental effect on basic saliva production. The idea of performing a two-stage autotransplantation of one submandibular gland to treat postradiotherapeutic xerostomia, as originally proposed by Spiegel et al [27,28,29], appeared to be a surgical approach with an acceptable perioperative risk in relation to the expected benefit. In order to keep the necessary operative intervention as low as possible, the first series was limited to HNSCC patients where standard therapy included the use of a free radial forearm flap (RFF).…”
Section: Discussionmentioning
confidence: 59%
“…Another critical point in the success of this procedure is the vicinity of the transplanted gland to the lymphatic drainage of the primary tumor region. Although it is known that, in contrast to the parotid gland the submandibular gland does not contain lymph nodes [29], there is still a certain risk of transferring malignant cells to the forearm during transplantation of the gland. But the possibility to spread microscopic metastases can be considered as very low since we only transplanted the gland and no surrounding soft tissue.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Spiegel et al [11] showed that nine patients of oral cavity squamous cell carcinoma had involved submandibular glands out of the 196 submandibular glands studied. Out of which, three submandibular glands showed invasion from a locally involved lymph node and six had direct extension from a primary lesion but no submandibular glands showed pathologic evidence of metastasis.…”
Section: Discussionmentioning
confidence: 98%